2014
DOI: 10.1016/j.neuroimage.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Cortical surface-based analysis reduces bias and variance in kinetic modeling of brain PET data

Abstract: Exploratory (i.e., voxelwise) spatial methods are commonly used in neuroimaging to identify areas that show an effect when a region-of-interest (ROI) analysis cannot be performed because no strong a priori anatomical hypothesis exists. However, noise at a single voxel is much higher than noise in a ROI making noise management critical to successful exploratory analysis. This work explores how preprocessing choices affect the bias and variability of voxelwise kinetic modeling analysis of brain positron emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
192
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 212 publications
(192 citation statements)
references
References 60 publications
0
192
0
Order By: Relevance
“…Leveraging high-resolution structural MRI (ϳ1 mm resolution) in combination with molecular images acquired with a high-resolution PET scanner with a resolution of 2 mm allows for precise segmentation of brain regions and accurate intersubject normalization. The surface-based approach used in this work has also been shown to lead to a reduction in bias and variance of PET-derived measurements (Greve et al, 2013). A main advantage of the surface-based method is to diminish partial volume effects introduced by smoothing in the volume; smoothing on the surface drastically reduces the blurring of neighboring tissues with cortical gray matter and blurring across adjacent gyri (Hagler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Leveraging high-resolution structural MRI (ϳ1 mm resolution) in combination with molecular images acquired with a high-resolution PET scanner with a resolution of 2 mm allows for precise segmentation of brain regions and accurate intersubject normalization. The surface-based approach used in this work has also been shown to lead to a reduction in bias and variance of PET-derived measurements (Greve et al, 2013). A main advantage of the surface-based method is to diminish partial volume effects introduced by smoothing in the volume; smoothing on the surface drastically reduces the blurring of neighboring tissues with cortical gray matter and blurring across adjacent gyri (Hagler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The pial surfaces were further refined using T2-weighted structural images and corrected manually where necessary. PET-MR coregistration was estimated using boundary-based registration (Greve and Fischl, 2009) between the timeweighted sum of the PET time-activity curves (TACs) and the structural MRI. Additionally, the transformation from individual MR space to normal MNI152 space was estimated with combined volume-surface (CVS) registration (Postelnicu et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As primary VOI analyses indicated that mainly cortical areas were related to GnRHa-induced depressive symptoms, we chose to conduct the analysis on a surface representation of cortex using FreeSurfer (version 5.1; A. Martinos Center for Biomedical Imaging, Boston, Massachusetts) by an approach described recently (41) and detailed in Supplement 1. Statistical analyses across subjects were performed by fitting general linear models independently at each surface node in standard space (MATLAB 8.1; Mathworks, Natick, Massachusetts).…”
Section: Surface-based Analysis Of Cortical Sert Bindingmentioning
confidence: 99%